Arachidonate 15-lipoxygenase type B: Regulation, function, and its role in pathophysiology - Benatzy, Yvonne; Palmer, Megan A.; Brüne, Bernhard (Frontiers in Pharmacology, 2022)
As a lipoxygenase (LOX), arachidonate 15-lipoxygenase type B (ALOX15B) peroxidizes polyenoic fatty acids (PUFAs) including arachidonic acid (AA), eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and linoleic acid (LA) to their corresponding fatty acid hydroperoxides. Distinctive to ALOX15B, fatty acid oxygenation occurs with positional specificity, catalyzed by the non-heme iron containing active site, and in addition to free PUFAs, membrane-esterified fatty acids serve as substrates for ALOX15B. Like other LOX enzymes, ALOX15B is linked to the formation of specialized pro-resolving lipid mediators (SPMs), and altered expression is apparent in various inflammatory diseases such as asthma, psoriasis, and atherosclerosis. In primary human macrophages, ALOX15B expression is associated with cellular cholesterol homeostasis and is induced by hypoxia. Like in inflammation, the role of ALOX15B in cancer is inconclusive. In prostate and breast carcinomas, ALOX15B is attributed a tumor-suppressive role, whereas in colorectal cancer, ALOX15B expression is associated with a poorer prognosis. As the biological function of ALOX15B remains an open question, this review aims to provide a comprehensive overview of the current state of research related to ALOX15B.